Load capability assessment and enhancement for transformers with integration of large-scale renewable energy: A brief review - Li, Shuaibing; Li, Xinchen; Kang, Yongqiang; Gao, Quanyi (Frontiers in Energy Research, 2022)
With the rapid development of large-scale distributed renewable energy in China, the load factor of distribution transformer increases year by year, this directly become a new challenge to the load capacity of the transformer. Once subjected to this condition for a long time will have an impact on the hotspot temperature and consequently, the useful life of the transformer. In this regard, load capacity assessment of the distribution transformer becomes an essential work for unit upgrading or even replacement. This article systematically summarized the evaluation methods of transformer load capacity, as well as the load capacity prediction and dynamic capacity enhancement strategies of transformer. Discussions for the future work regarding this topic are also carried out.